An Identity-Based Model Explaining Online Donor Appreciation. Issue 1 (February 2023) - Chell, Kathleen; Mortimer, Gary; Masser, Barbara M.; Russell-Bennett, Rebekah
Nonprofit organization (NPO) marketers are now increasingly turning online to recognize donors, with little understanding as to how online donor appreciation influences behavior. A scenario-based research design using an online survey was administered to a random sample of voluntary blood donors ( n  = 356). The findings contribute to identity theory by demonstrating that online recognition (digital badge shared to Facebook) can strengthen subjective impressions of identity-related behavior above a private thank-you email alone. Furthermore, outcomes of a positive identity appraisal (accountability and emotional value) were found to differentially drive NPO-benefiting activities (positive electronic word-of-mouth and donation intentions) depending on donation experience. The results strategically inform online donor appreciation activities to improve donor retention.